Komorbiditas Fisik pada Gangguan Bipolar di RS. Dr. H. Marzoeki Mahdi Bogor - Tinambunan, Iriawan Rembak; Amir, Nurmiati; Budiman, Richard; Kusumaningrum, Profitasari (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Bipolar disorders are known to cause various clinical comorbidity that may affect work, family and interpersonal function. Two third of bipolar disorder have comorbidities that may worsen the outcome of bipolar itself and interfere with it’s therapy. There has not been sufficient study about physical comorbidities in bipolar in Indonesia. As the oldest psychiatric hospital in Indonesia that treats physical and psychiatric inpatients, Dr. H. Marzoeki Mahdi hospital still lacks data concerning types and frequencies of physical comorbidities. Method: This research uses cross-sectional design from 100 people with bipolar disorder at Psychiatric Clinic and Psychiatric Ward at Dr. H. Marzoeki Mahdi Bogor Hospital. This research also uses the Structured Clinical Interview For the DSM-IV Axis I Disorders to ensure the bipolar diagnosis, and criteria diagnostic for ten physical comorbidities from each of their field. Result: There is a significant relationship in this research between age and physical comorbidities p=0.001 (p less-than 0,005). In the additional analysis, there are significant relationship in this research between polypharmacy / monotherapy and hypertension (p=0,0001). Migraine, hypertension, and dermatitis were the top three physical comorbidities in this research. Conclusion: Hypertension, migraine and dermatitis are the top three in our physical comorbidities in Dr. H. Marzoeki Mahdi hospital. Age has a significant relationship with physical comorbidities. Polipharmacy and monotherapy also has significances in hypertension. Therefore psychiatrist must be aware about the possibility of physical comorbidity in the psychiatric care.